2018
DOI: 10.13080/z-a.2018.105.041
|View full text |Cite
|
Sign up to set email alerts
|

The productivity, quality and bread-making properties of organically and conventionally grown winter rye

Abstract: Rye in combination with wheat is the major bread grain in northern Europe. Consuming rye whole grain products provides a rich source of dietary fibre as well as several bioactive compounds with potentially positive health implications. Due to limited research data concerning rye growing under different cultivation systems, there is also a lack of information on the influence of these systems on the quality properties of rye breads. The goal of the research was to compare the responses of rye to the conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The protein content of wholemeal flour (9.59%) and extracted flour (5.91%) from primitive rye grain was significantly higher in comparison with the corresponding flours from open-pollinated rye and was similar to hybrid rye flours. The protein content of primitive rye flours was typical of rye flour (Konopka et al 2017b ; Järvan et al 2018 ). The total protein content of rye is generally lower in comparison with wheat (6.5–14.5% on average) (Arendt and Zannini 2013 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The protein content of wholemeal flour (9.59%) and extracted flour (5.91%) from primitive rye grain was significantly higher in comparison with the corresponding flours from open-pollinated rye and was similar to hybrid rye flours. The protein content of primitive rye flours was typical of rye flour (Konopka et al 2017b ; Järvan et al 2018 ). The total protein content of rye is generally lower in comparison with wheat (6.5–14.5% on average) (Arendt and Zannini 2013 ).…”
Section: Resultsmentioning
confidence: 98%
“…The thousand-kernel weight (TKW) of primitive rye was low (21.6 g) compared with common rye cultivars, and its bulk density was determined at 756.3 kg m −3 . The kernels weight is dependent on the growth conditions and cultivar (Järvan et al 2018 ). Primitive rye grain did not differ significantly in width (2.48 mm) from the grain of open-pollinated and hybrid cultivars, but it was characterized by smaller average kernel length (6.69 mm).…”
Section: Resultsmentioning
confidence: 99%
“…showed that all purified cereal glucan appeared only one peak at the same Retention time RT of standard oat glucan which ranged between 17.429 to 17.453 min that may give somewhat an indication about the purity of the prepared cereal glucan. Also, Abd El Ghany, et al (14) identified peak of (1→3)(1→6)-β-Dglucan extracted from Pediococcus parvulus by using HPLC, had retention time at 9.044 min. The results also showed that all the purified extracted cereal -glucan have the same RT either between the tested -glucan or with standard -glucan was about 17.45 min.…”
Section: Comparison Between Purified Glucan and Standard Oat Glucanmentioning
confidence: 99%